Peptide-specific recognition of human cytomegalovirus strains controls adaptive natural killer cells - Hammer, Q; Rückert, T; Borst, EM; Dunst, J; Haubner, A; Durek, P; Heinrich, F; Gasparoni, G; Babic, M; Tomic, A; Pietra, G; Nienen, M; et al. (Springer Nature, 2018)
Natural killer (NK) cells are innate lymphocytes that lack antigen-specific rearranged receptors, a hallmark of adaptive lymphocytes. In some people infected with human cytomegalovirus (HCMV), an NK cell subset expressing the activating receptor NKG2C undergoes clonal-like expansion that partially resembles anti-viral adaptive responses. However, the viral ligand that drives the activation and differentiation of adaptive NKG2C+ NK cells has remained unclear. Here we found that adaptive NKG2C+ NK cells differentially recognized distinct HCMV strains encoding variable UL40 peptides that, in combination with pro-inflammatory signals, controlled the population expansion and differentiation of adaptive NKG2C+ NK cells. Thus, we propose that polymorphic HCMV peptides contribute to shaping of the heterogeneity of adaptive NKG2C+ NK cell populations among HCMV-seropositive people.